24. A CHANGE IN DEVELOPMENT FROM THE BOTTOM UP, FROM SIMPLICITY TO COMPLEXITY (IN THE EXAMPLE OF RAILWAY TRANSPORT) - Salimov Bakhriddin Lutfullaevich. O’ktamov Asadbek Baxromovich (Innovative technologies in construction Scientific Journal, 2023)
In the article, the demand to change steam locomotives to diesel locomotives and, in turn, diesel locomotives to a new form of transport, is on the agenda, because the economic efficiency of diesel locomotives, which were once a novelty, has been decreasing year by year. It has been analyzed that such situations require the modernization of railway transport, and one of the works in this direction is to start using electric locomotives instead of diesel locomotives.